- Thread starter harpazo
- Start date

\(\displaystyle \dfrac{(4x)(y) - (2)(5x)}{(2)(y)} = \dfrac{(4x)(y)}{(2)(y)} - \dfrac{(2)(5x)}{(2)(y)}\)

Cancel out stuff.

\(\displaystyle \dfrac{4x}{2} - \dfrac{5x}{y} = \dfrac{2x}{1} - \dfrac{5x}{y}\)

\(\displaystyle \frac{4x}{2}-\frac{5x}{y}=\frac{2x}{1}-\frac{5x}{y}=\frac{2xy-5x}{y}=\frac{x}{y}(2y-5)\)

Thanks. I will try again.What you've ended up with is not equivalent to that with which you began. You multiplied the expression by \(2y\) which changes it.